KAJIAN GEOGRAFI EKONOMI: STUDI KASUS KONDISI SOSIAL EKONOMI MASYARAKAT SUKU BAJO DI POPAYATO, GORONTALO - Wiwin Kobi; Hendra Hendra (JAMBURA GEO EDUCATION JOURNAL, 2020)
The purpose of this study was to analyze the conditions and forms of social and economic interaction of the Bajo people in Pohuwato Regency. This study uses a qualitative descriptive approach. The results showed that the social and economic conditions of the Bajo tribe had a low level of health and education in the Torosiaje Jaya and Bumi Bahari villages. In the village of Torosiaje, the level of environmental awareness is still lacking. In terms of work, they work as fishermen, the income is higher in the Torosiaje Village compared to the income in the Torosiaje Jaya Village and Bumi Bahari Village, which is classified as poor. The social-economic characteristics of the Bajo in the Torosiaje village in terms of education and health are still low. While income is high. In the village of Torosiaje Jaya in terms of education and health is low. But environmental awareness is high. Some work as fishermen and some choose other workers. Her income is low and belongs to the poor category. In the village of Bumi Bahari in terms of education and health is still low. But environmental awareness is high. Some work as fishermen, some choose other jobs. Income is low and belongs to the poor category. The social interaction carried out by the Bajo is generally good. With the characteristics of rural interaction that relies on cooperation and mutual help to help fellow Bajo and Bajo tribes with the surrounding community.